Compañía, buenos días, de pie. Construcción del cuerpo militar (2018)
This work takes place in Escuela Militar de Cadetes Jose Maria Cordova in Bogota, where from an ethnographic work of participant observation, interviews and image capture for more than a year (2014-2015), responds to concerns on how the cadets prepare their bodies in the institution to achieve the title of second lieutenants of the National Army. The institution is in a cyclical time related to post-conflict and respect for human rights that have transformed the structure of military education according to the new needs of the institution. Comprehensive training is currently looking in order to teach the cadets basic ways such as eating, sleeping, bathing, strategic use of arms and university training, all during four years of ongoing formation where the body of the young men is constructed as a reflection of the Army.